2010
DOI: 10.1369/jhc.2010.956300
|View full text |Cite
|
Sign up to set email alerts
|

Spexin Expression in Normal Rat Tissues

Abstract: Spexin is a highly conserved peptide which was recently identified through the bioinformatics approach. Immunohistochemical analysis of its expression has not yet been performed. Thus, in this study, we examined spexin location in a wide range of rat organs by both RT-PCR and IHC. RT-PCR identified spexin mRNA in all tissues examined. Spexin immunoreaction was mainly cytoplasmic. Spexin was immunohistochemically detected, although with different staining intensities, in epithelia and glands of skin and respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(106 citation statements)
references
References 22 publications
7
98
0
1
Order By: Relevance
“…Consistent with the recent report on tissue expression profiling in the rat (25), SPX was found to be expressed ubiquitously in goldfish. The widespread pattern of SPX distribution is in agreement with the pleiotropic functions of SPX reported in different tissues in mammals.…”
Section: E362supporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with the recent report on tissue expression profiling in the rat (25), SPX was found to be expressed ubiquitously in goldfish. The widespread pattern of SPX distribution is in agreement with the pleiotropic functions of SPX reported in different tissues in mammals.…”
Section: E362supporting
confidence: 91%
“…Consistent with the high levels of transcript expression in different brain areas, protein expression of SPX was also confirmed by LC/MS-MS in protein pulldown prepared from goldfish brain lysate, using the antiserum for SPX mature peptide. In the rat, SPX transcripts and SPX protein expression could be located in brain areas, including the cerebral cortex, hypothalamus, cerebellum, and brain stem (25). Given that SPX immunoreactivity was also detected in the cytoplasm of neuronal cells in these brain areas, it is likely that SPX may function as a neurotransmitter/neuromodulator within the CNS.…”
Section: E363 Structure and Function Of Goldfish Spexinmentioning
confidence: 99%
See 1 more Smart Citation
“…Porzionato et al [1] showed the expression of spexin in various rat tissues such as the hypothalamus, pons, cerebral cortex, kidney, ovary, adrenal gland, thyroid, anterior pituitary, and stomach. The expression of spexin in endocrine cells suggested its possible role as an endocrine factor [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, many SPX immunopositive neural populations have been described, while neuroglia are usually negative, the highest reaction was detected in the hypothalamic paraventricular and supraoptic nuclei. Hippocampal neurons show moderate immunoreactivity as well as cerebellar Purkinje cells and brainstem neurons [6].…”
Section: Spexin (Spx) Is One Such Intriguing Novel Neuropeptide a Prmentioning
confidence: 99%